Navigating old and new terrains of academic practice in higher education: indelible and invisible marks left from the Covid-19 lockdown (UCL Press, 2023)
Higher education has been (re)shaped by the Covid-19 pandemic in ways which have left both indelible and invisible marks of that period. Drawing on relevant literature, and informed by an exchange catalysed through a visual narrative method, authors from four European universities engage with two reflective questions in this article: As academics, what were our experiences of our practice during the lockdown periods of the Covid-19 pandemic? What might we carry forward, resist or reimagine in landscapes of academic practice emerging in the post-Covid future? The article explores how academics experienced and demonstrated resilience and ingenuity in their academic practice during that turbulent time. Particular insights include entanglements of the personal and professional, and the importance, affordances and limitations of technology. In addition, the authors reflect on some of the ongoing challenges exacerbated by the pandemic, such as education inequalities. The article concludes by reprising the key points about what marks are left behind in the post-Covid present, and how these relate to the future in which relational pedagogy and reflexivity are entangled in the ways in which we cohabit virtual and physical academic spaces.